Study of Amino ligands fixation to Macroporous supports and their influence on Albumin adsorption - Gomez, Cesar Gerardo (2009)
Heterogeneous networks of ethylene glycol dimethacrylate and 2-hydroxyethyl methacrylate [poly(EGDMA-co-HEMA)] were synthesized by suspension polymerization using different EGDMA contents and agitation speeds. The networks were actived with epichlorhydrine (Ech) or 1,4-butanediol diglycidyl ether (BDGE), and then hexamethylenediamine (HMDA) or ethylenediamine (EDA) were conjugated to the support by coupling reaction. Here, a higher alkyldiamine concentration and temperature, and a longer reaction time led to higher yields. Amino ligands of the support III were used to analyze their adsorption performance of bovine serum albumin (BSA) from the adsorption kinetic. A more external location of HMDA amino ligands into network led to get the maximum adsorption in a time shorter than that with EDA. Due to its bigger size, the HMDA molecule was attached mostly to the network surface between larger pores, which favored a faster protein adsorption. When derivatives containing BDGE were compared, the EDA ligand displayed a BSA retention higher than that with HMDA, because a shorter separation between the ammonium groups along the spacer arm yielded a stronger electrostatic attraction on the protein. Clearly, the balance obtained between the pores system and the reagents molecular structure used in the formation of Ech-HMDA generated the most efficient BSA adsorption.